Respuesta :

Answer:

C.

Step-by-step explanation:

Simply add the two functions.

5x³+2x²-7x+4

+            3x-7

Everything with an exponent stays the same because there is nothing else with those exponents in the other function. So all you're doing is adding the -7x+4 and 3x -7.

-7x+3x = -4x

4 - 7 = -3

That leaves you with answer C:

5x³+2x²-4x-3

Answer:

[tex]C.(f+g)(x)=(5x^3+2x^2-4x-3)[/tex]

Step-by-step explanation:

[tex]We\ are\ given\ that,\\f(x)=5x^3+2x^2-7x+4\\g(x)=3x-7\\Hence,\\(f+g)(x)\\=f(x)+g(x)\\Hence,\\f(x)+g(x)=(5x^3+2x^2-7x+4)+(3x-7),\\ f(x)+g(x)=(5x^3+2x^2-7x+3x+4-7) \\f(x)+g(x)=(5x^3+2x^2-4x-3)\\Hence,\\(f+g)(x)=(5x^3+2x^2-4x-3)[/tex]

ACCESS MORE